2009
DOI: 10.1371/journal.ppat.1000593
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus 71 3C Protease Cleaves a Novel Target CstF-64 and Inhibits Cellular Polyadenylation

Abstract: Identification of novel cellular proteins as substrates to viral proteases would provide a new insight into the mechanism of cell–virus interplay. Eight nuclear proteins as potential targets for enterovirus 71 (EV71) 3C protease (3Cpro) cleavages were identified by 2D electrophoresis and MALDI-TOF analysis. Of these proteins, CstF-64, which is a critical factor for 3′ pre-mRNA processing in a cell nucleus, was selected for further study. A time-course study to monitor the expression levels of CstF-64 in EV71-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
119
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(121 citation statements)
references
References 57 publications
2
119
0
Order By: Relevance
“…We along with others have reported that 3C can mediate cleavage of host factors and affect their functions (12,35,36). To investigate whether EV71 3C targets GSDMD, we conducted cleavage experiments.…”
Section: Resultsmentioning
confidence: 99%
“…We along with others have reported that 3C can mediate cleavage of host factors and affect their functions (12,35,36). To investigate whether EV71 3C targets GSDMD, we conducted cleavage experiments.…”
Section: Resultsmentioning
confidence: 99%
“…EV71 3C is a multifunctional protein which is essential for viral replication. In addition to its role in viral protein processing, the 3C protein induces apoptosis and inhibits cellular polyadenylation (27,32,46,50). It is notable that the 3C protein bears proteolytic and RNA binding activities.…”
Section: Discussionmentioning
confidence: 99%
“…This is noticed at the level of transcription, mRNA processing, nucleocytoplasmic transport, translation, or RNA granules composition. Among other proteins, proteolysis affects splicing factors, RNAprocessing proteins, RNA helicases, nuclear pore factors, stress granules assembly factors or antiviral response proteins (Almstead and Sarnow, 2007;Barral et al, 2009;Castello et al, 2009;Chen et al, 2013;Lawrence et al, 2012;Mukherjee et al, 2011;Park et al, 2010;Pineiro et al, 2012;Rozovics et al, 2012;Shiroki et al, 1999;Watters and Palmenberg, 2011;Weng et al, 2009;White et al, 2007).…”
Section: Picornavirus-induced Modification Of Host Factorsmentioning
confidence: 99%